STANDARDISATION OF LEAVES OF MALLOTUS PHILIPPENSIS LAM.) MUELL. ARG. AS PER WHO GUIDELINES - SELLAPERUMAL SATHYA,; AYARIVAN PURATCHIKODY, (International Journal of Pharma and Bio Sciences, 2015)
The standardization of Leaves of Mallotus philippensis (Lam.) Mull. Arg. was carried out according to the quality control methods suggested by WHO. The powder material was tested for various parameters like macroscopy, microscopy, foreign matter, ash value, extractable matter, crude fibre content, moisture content, swelling index, foaming index, pesticide residues, Arsenic and heavy metals, microbial contamination etc. The preliminary phytochemical screening showed the presence of amino acids, phenolic compounds, proteins, steroids, terpenoids and carbohydrates in various extracts. The material was free from microbial contamination. The TLC profile of extracts showed the presence of saponins, flavonoids, bitter principles, acidic metabolites, cardiac glycosides and alkaloids.The HPTLC studies showed the presence of 16 numbers of compounds.